EAGE Annual Conference &Amp; Exhibition Incorporating SPE Europec 2013
DOI: 10.2118/164869-ms
|View full text |Cite
|
Sign up to set email alerts
|

Well Deliverability Forecasting of Gas Condensate and Volatile Oil Wells below Saturation Pressure

Abstract: Development of a condensate bank in gas condensate wells producing below the dew point pressure causes productivity losses as gas mobility at the wellbore is reduced. The same is true in volatile oil wells producing below the bubble point pressure due to the existence of a gas bank. Using compositional simulation, this paper investigates the use of back-pressure plots expressed in terms of pressure, singlephase pseudo-pressure, and two-phase pseudo-pressure to describe well productivity losses b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In gas condensate reservoirs, a fourth region may also exist in the vicinity of the wellbore where low interfacial tension at high velocities causes decrease in oil saturation and increase in relative permeability of gas (Gringarten et al 2000). Later studies showed that this effect is more pronounced with gas condensate fluids than with volatile oils (Ogunrewo et al 2013). However, since there is no firm understanding about the existence of this region in volatile oil reservoirs (Sharifi and Ahmadi 2009;Sanni and Gringarten 2008), it is not considered in the present study.…”
Section: Introductionmentioning
confidence: 88%
“…In gas condensate reservoirs, a fourth region may also exist in the vicinity of the wellbore where low interfacial tension at high velocities causes decrease in oil saturation and increase in relative permeability of gas (Gringarten et al 2000). Later studies showed that this effect is more pronounced with gas condensate fluids than with volatile oils (Ogunrewo et al 2013). However, since there is no firm understanding about the existence of this region in volatile oil reservoirs (Sharifi and Ahmadi 2009;Sanni and Gringarten 2008), it is not considered in the present study.…”
Section: Introductionmentioning
confidence: 88%
“…Three sets of volatile oil reservoirs have been developed. Compared with the components of traditional black oil and condensate gas, the main feature of volatile oil is that the content of intermediate hydrocarbons (C2-C6) is much higher than that of black oil and condensate gas [1]. The content of light component (C1) and heavy component (C7+) is between black oil and condensate gas.…”
Section: Crude Oil Composition and Phase Analysismentioning
confidence: 99%